ANALISIS PENGARUH LUAS LAHAN, MODAL DAN BIAYA TENAGA KERJA TERHADAP TINGKAT PENDAPATAN PETANI GARAM DI DESA - Ferlinda Wardani Asrini (Program Studi Ekonomi Pembangunan, 2019)
This study aims to analyze the effect of land area, capital and labor costs on the income level of salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency. The research data were obtained from a questionnaire (primary) with a population of 312 salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency. A sample of 47 salt farmers was taken using purposive sampling technique. The data analysis used multiple linear regression model which was tested using simultaneous test and partial test and classical assumption test. The results showed that the land area (X1) had a significant effect on the income of salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency. Capital (X2) has a significant effect on the income of salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency. Labor costs (X3) have a significant effect on the income of salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency.